2018
DOI: 10.3389/fcvm.2018.00076
|View full text |Cite
|
Sign up to set email alerts
|

Indexed Left Atrial Adipose Tissue Area Is Associated With Severity of Atrial Fibrillation and Atrial Fibrillation Recurrence Among Patients Undergoing Catheter Ablation

Abstract: Background: Epicardial adipose tissue (EAT) has been associated with adverse left atrial (LA) remodeling and atrial fibrillation (AF) outcomes, possibly because of paracrine signaling.Objectives: We examined factors associated with a novel measure of EAT i.e., indexed LAEAT (iLAEAT) and its prognostic significance after catheter ablation (CA) of atrial fibrillation (AF).Methods: We performed a retrospective analysis of 274 participants with AF referred for CA. LAEAT area was measured from a single pre-ablation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 40 publications
1
11
1
1
Order By: Relevance
“…The different technical protocols or procedures of CA may result in different cutoff values for atrial volume and atrial EAT volume in predicting AF recurrence. Our values of EAT volume were smaller than those of Sanghai et al 25 and Nagashima et al 2 , but the EAT volume may differ according to the machine accuracy of MDCT, the measurement method, the extent of measurement around the heart, and the time course of persistent AF 26 . However, the EAT volume in the present study was measured in a similar manner to the report by Shin et al 12 , and our values were similar to their values mean total heart EAT in patients with paroxysmal AF, 86 ml vs. 76.6 ml .…”
Section: Study Limitationscontrasting
confidence: 73%
See 1 more Smart Citation
“…The different technical protocols or procedures of CA may result in different cutoff values for atrial volume and atrial EAT volume in predicting AF recurrence. Our values of EAT volume were smaller than those of Sanghai et al 25 and Nagashima et al 2 , but the EAT volume may differ according to the machine accuracy of MDCT, the measurement method, the extent of measurement around the heart, and the time course of persistent AF 26 . However, the EAT volume in the present study was measured in a similar manner to the report by Shin et al 12 , and our values were similar to their values mean total heart EAT in patients with paroxysmal AF, 86 ml vs. 76.6 ml .…”
Section: Study Limitationscontrasting
confidence: 73%
“…Sanghai et al 25 showed that a LA EAT volume>0.95 cm 2 /body surface area m 2 using a 128-slice MDCT had a sensitivity of 45 and a specificity of 25.5 for predicting AF recurrence over 12 months of follow-up in patients with mixed AF. In a population of patients with mixed AF at a median follow-up time of 10.2 months, Nagashima et al 2 showed that a 320-slice MDCT LA EAT volume>63.4 cm 3 was predictive of AF recurrence, with a sensitivity of 60.0 and a specificity of 96.0 .…”
Section: Diagnostic Accuracy Of Ra Eat For Predicting Af Recurrencementioning
confidence: 99%
“…Obesity is associated with increased thickness of epicardial adipose tissue (the fat that lies directly adjacent to the epicardium underneath the pericardium), which can have profound consequences on atrial electrophysiology and promote arrhythmogenesis (Abed et al, 2013; Mahajan et al, 2015; Evin et al, 2016). Indeed, increases in epicardial adipose tissue have been found to associate with adverse left atrial remodeling and increased incidence of AF, supporting the idea that epicardial adipose tissue could play an important role in the pathophysiology of AF (Sanghai et al, 2018). Coinciding with the increased epicardial adipose tissue volume, fatty infiltration of the atrial epicardium is also increased (Mahajan et al, 2015).…”
Section: Mechanisms Of Af In Dm: Insights From Experimental Studiesmentioning
confidence: 71%
“…Several groups, including ours, have shown correlation between EAT and onset as well as severity of AF. Our group has previously shown that an indexed measure of EAT surrounding the left atrium, called iLAEAT, is independently associated with the severity and recurrence of AF after catheter ablation (14).…”
Section: Introductionmentioning
confidence: 99%